JUCAMA learning model: A pathway to improved mathematical communication - Leni Agustina Daulay; Cut Latifah Zahari; Rosliana Harahap; Dewi Riani (State Islamic University of North Sumatra, 2025)
Mathematical communication is a fundamental competence that enables students to express, interpret, and justify mathematical ideas clearly; however, many junior high school students still demonstrate low proficiency in this skill. This study examines the effect of the Problem Submission and Solving (JUCAMA) learning model on students